Epidemiology of methicillin‐resistant Staphylococcus aureus carrying the novel mecC gene in Denmark corroborates a zoonotic reservoir with transmission to humans. (19th October 2012) - Petersen, A.; Stegger, M.; Heltberg, O.; Christensen, J.; Zeuthen, A.; Knudsen, L. K.; Urth, T.; Sorum, M.; Schouls, L.; Larsen, J.; Skov, R.; Larsen, A. R.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract Methicillin‐resistant Staphylococcus aureus (MRSA) is a major cause of healthcare‐associated (HA), community‐associated (CA) and livestock‐associated (LA) infections. Recently, the discovery of human and bovine MRSA isolates carrying a new mecA gene homologue, mecALGA251 (now designated mecC), has caused concern because they are not detected by conventional, confirmatory tests for MRSA. Very little is known about their frequency, epidemiology and possible transmission between livestock and humans. In this study, the epidemiology of the mecC isolates in Denmark was investigated by screening the national collections of MRSA cases (from 1988 onwards) and S. aureus bacteraemia cases (from 1958 onwards). Isolates carrying mecC were only recovered infrequently before 2003 (n = 2) but now seem to be increasing, with 110 cases in 2003–2011. Clinical data on mecC‐carrying MRSA demonstrated that mecC‐MRSA were primarily community‐acquired (CA‐MRSA) and affected persons typically living in rural areas, being older than other CA‐MRSA patients. Among 22 cases in Region Zealand, four reported contact with cattle and sheep. Two of these persons lived on farms with livestock positive for mecC‐carrying MRSA, sharing spa type (t843), MLVA (MT429) and PFGE pattern with the human isolates. These observations indicate that mecC‐carrying MRSA can be exchanged between humans and ruminants.